Maritime Security Strategy Against Illegal Fishing in Riau Indonesia - Novia Ayu Rizky; Widodo Widodo; Bayu Asih Yulianto; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (CV. AFDIFAL MAJU BERKAH, 2023)
Riau is a province prone to illegal fishing activities which are harmful to the state. This is due to the lack of optimisation of its marine potential, which then became exploited by foreign fishermen. This research will discuss the strategy employed by the Marine and Fisheries Department of Riau (Dinas Kelautan dan Perikanan/DKP) in combating illegal fishing in Riau waters. This paper argues that the strategy is to engage with local communities, increase technical and human capital, and perform patrols by engaging with stakeholders such as PSDKP, Polair, and TNI AL. This research uses the descriptive qualitative method, and the data is collected through interviews (via Zoom meeting) with DKP Riau, to discover the right strategies in combating illegal fishing in Riau to promote maritime security. This research discloses that the necessary strategies are to increase the number of workers, facilities, and infrastructures for maritime surveillance to engage with local communities, in this case, the Monitoring Community Group (Kelompok Masyarakat Pengawas/Pokmaswas), by supporting the government in monitoring and deterring threats towards Indonesian marine resources; to implement policies for prosecution; and to increase maritime patrols like synergy between DKP Riau and other government agencies for the process of monitoring and arresting carried out due to the lack of facilities owned by DKP Riau. The joint patrols for inspecting marine and fishery resources are carried out in collaboration with DKP, Satpol PP, TNI AL, and Polair.